Electrically Tunable Gyrohelitrons with Crossed Fields - A. A. Kurayev; V. V. Matveyenka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
The generation frequency is ω ≈ kωн in classical gyrotrons, where ωн = еB0/m is the electron cyclotron rotation frequency in a uniform longitudinal magnetic field with induction B0, e is the electron charge, m is the electron mass, k = 1, 2, 3… is the cyclotron frequency working harmonic number. Thus, the generation frequency ω being tuned is possible only by changing B0. This way is very inconvenient. It’s necessary a solenoid additional (control) winding. That difficulty can be eliminated in gyrotrons with crossed fields - electric 0 and magnetic 0, here 0 ⊥ 0. The frequency can be tuned by changing E0. This possibility can be realized at least two ways: a gyrotron based on a coaxial resonator with radial field E0; a four-mirror gyrotron on traveling Т-waves with transverse in respect the traveling wave direction to uniform crossed fields – electric 0 and magnetic 0. The single-screw electron flow has a rotation frequency , for the first gyrotron type, where , , ΔV is the potential difference between the inner (radius b1) and outer (radius b2) coaxial conductors, r0 is the electron flow rotation radius. Thus, the generation frequency ω ≈ kωн is determined by both B0 and ΔV. Moreover, at ΔV = 0 the device becomes a classical high-orbit gyrotron, at B0 = 0 a classical helitron. Therefore, at B0 ≠ 0 and ΔV ≠ 0 it should be called a gyrohelitron, the generation frequency of which is tuned electrically - by changing ΔV. The article presents the design schemes of a gyrohelitron and a two-beam four-mirror gyrotron. In both cases, piezoelectric devices realize synchronous tuning of the frequency, just it allows the devices becoming fully electrically controllable. The following results were obtained for the gyrohelitron. Resonator field – H211, interaction on the second harmonic ωs; a) narrow-band tuning 10 %: maximum efficiency – 55 %, minimum efficiency – 25 %; β0 = v0/c = 0.27; q = v0⊥/v|| = 2; b) broadband tuning 58 %: maximum efficiency – 18 %, minimum efficiency – 14 %; β0 = v0/c = 0.2; q = v0⊥/v|| = 2. The given results for the gyrohelitron indicate that it is promising to use electrical frequency tuning in a coaxial gyro-BWT and the amplification band in a gyro-TWT, since these devices do not require piezoelectric tuning of electrodynamic structures.